The Politics of Memory in the Context of International Relations (On the Example of the G.K. Zhukov Museum in Mongolia) - A. V. Mikhalev (Сравнительная политика)
The article sheds light on memory politics in Mongolia. It focuses on the memorial complex dedicated to G.K. Zhukov, which includes a museum, a monument and a street. The research design is tailored to identify the ways of using history for political purposes. The study draws on three groups of empirical sources, that are the author’s personal observations, the publications in Mongolian and Russian media as well as public statements made by the heads of states. The paper analyses how the political status of the memorial has evolved since the 20th century, by emphasizing different cultural and political meanings attached to the exposition and the facade of the museum. The article also considers commemoration practices associated with the memorial complex. The study concludes that the inclusion of the museum in the sphere of public commemoration at the head-of-state level is linked to the restoration of military and political cooperation between Russia and Mongolia in 2008.